Pengembangan metode penanda genetika molekuler untuk lacak balak (studi kasus pada jati) - Iskandar Z. Siregar; Ulfah J. Siregar; Lina Karlinasari; Tedi Yunanto (Jurnal Ilmu Pertanian Indonesia, 2008)
Tracking timber on teak and teak wood products can be conducted using different methods, such as DNA finger printing, chemical composition of the wood, Near Infra Red spectra (NIR) and stable isotopes. Samples were collected from wood material and leaves in Java (9 Forest Management Units district) of Perhutani to determine: i) pattern of genetic variation within and among populations, ii) to determine the protocol for DNA extraction from wood, and iii) to study the feasibility of DNA marker for timber tracking in the field. Results show that: i) genetic variation of cpDNA (PCR-RFLP) is low, while RAPD variation is moderate, ii) there are differences in chemical composition of wood among the Forest Management Units (FMUs) of Perhutani, iii) variation of isotopic carbon and oxygen in Central and East Java were higher than from of West Java, iv) absorbtion intensity of NIR in West Java was higher than for Central and East Java, and iv) testing of DNA marker showed that genetic structure in the forest site is not significantly different from that in log yards, indicating that the timber flow is still according to the procedure. RAPD marker also is able to determine the origin of illegal timber and wood in industry without clear identity. Keywords: genetik marker, teak, timber tracking